ANALISIS PENGARUH STRES KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. HARAPAN CITRA JAYA - Ida Lora; Tibrani Tibrani; Sriwati Sriwati (EQUILIBIRIA, 2016)
Principal research that you want to answer through this study is: Does work stress has direct influence on the performance of the employee, whether compensated directly influence employee performance. Does work stress affect the performance and compensation of employees simultaneously and partially PT. Harapan Citra Jaya. Results of this study, ie work stress directly affects the performance of employees based on the perception of 100 people scored 3,773 or (20.4%). compensation to employee performance scored 3,173 or (14.5%). So also with the stress of work and the compensation effect on the performance of the employees got together with the 7154 value (65.1%). From the analysis also found that it can be compared directly influence the three variables: the stress of work, compensation and performance of employees have an equally strong influence.